(untitled) (Czech Journal of International Relations, 2024)
Harvey Sicherman: former advisor to three US secretaries of state (A.M. Haig, G.P. Shultz, J.A. Baker), currently president of the Foreign Policy Research Institute (FPRI) in Philadelphia. He is the author of a number of books, e.g. Palestinian Self-Government (Autonomy): Its Past and Its Future (Westview Press 1992), The Three Percent Solution and the Future of NATO (FPRI 1981). He mainly deals with issues of the Middle East and Western Europe and the world economy.